THE EFFECT OF TAX SUPERVISION AND TAX COLLECTION ON OBEDIENCE TO PAY TAXES AND TAX REVENUE - Basrowi (School of Accountancy, University of Agung Podomoro, 2019)
The purpose of this study was to determine the effect of tax supervision and tax collection both partially and simultaneously on the compliance of taxpayers and their implications for tax revenue. The type of research used in this study is a type of causality research, namely research that aims to determine the effect of independent variables on the dependent variable. However, the method used in this research is a quantitative approach. The data collection technique used in this study is by using secondary data from the Pratama Tax Office of Lampung Province, specifically from the Inspection Section and the 2017 and 2018 Billing Section. Data were analyzed using the SPSS version 18 and Lisrel programs. Based on the results of data analysis it was concluded that there were significant effects both partially and simultaneously between tax supervision, tax collection, taxpayer compliance with tax revenue.